(untitled) (Clinics, 2015)
OBJECTIVE: To compare high-fidelity simulation with case-based discussion for teaching medical students about pediatric emergencies, as assessed by a knowledge post-test, a knowledge retention test and a survey of satisfaction with the method. METHODS: This was a non-randomized controlled study using a crossover design for the methods, as well as multiple-choice questionnaire tests and a satisfaction survey. Final-year medical students were allocated into two groups: group 1 participated in an anaphylaxis simulation and a discussion of a supraventricular tachycardia case, and conversely, group 2 participated in a discussion of an anaphylaxis case and a supraventricular tachycardia simulation. Students were tested on each theme at the end of their rotation (post-test) and 4-6 months later (retention test). RESULTS: Most students (108, or 66.3%) completed all of the tests. The mean scores for simulation versus case-based discussion were respectively 43.6% versus 46.6% for the anaphylaxis pre-test (p=0.42), 63.5% versus 67.8% for the post-test (p=0.13) and 61.5% versus 65.5% for the retention test (p=0.19). Additionally, the mean scores were respectively 33.9% versus 31.6% for the supraventricular tachycardia pre-test (p=0.44), 42.5% versus 47.7% for the post-test (p=0.09) and 41.5% versus 39.5% for the retention test (p=0.47). For both themes, there was improvement between the pre-test and the post-test (p;0.05). Moreover, the satisfaction survey revealed a preference for simulation (p